Can Patients with Parkinson’s Disease Use Dry Powder Inhalers during Off Periods? - Luinstra, M. (PLoS One, 2015)
Because of its rapid onset of action, pulmonary administration of levodopa is an interesting alternative to oral administration for the rescue treatment of Parkinson’s disease patients in an off period. We studied the ability of Parkinson’s disease patients to operate a dry powder inhaler (DPI) correctly during an off period. We used an instrumented test inhaler with three different resistances to air flow to record flow curves and computed various inhalation parameters. We observed that all (13) patients were able to generate pressure drops > 2 kPa over the highest resistance and 10 out of 13 patients achieved at least 4 kPa. Inhaled volumes (all resistances) varied from 1.2 L to 3.5 L. Total inhalation time and the time to peak inspiratory flow rate both decreased with decreasing inhaler resistance. Twelve out of thirteen patients could hold their breath for at least five seconds after inhalation and nine could extend this time to ten seconds. The data from this study indicate that patients with Parkinson’s disease will indeed be able to use a dry powder inhaler during an off period and they provide an adequate starting point for the development of a levodopa powder inhaler to treat this particular patient group.